Community Engagement, Trust, and Genetic Testing for Inherited Diseases Among Adopted Persons - Kaija L. Zusevics; Kimberly Strong; Michael McCauley; Alison La Pean Kirschner; Jessica Jeruzal; Samantha Wilson; Carmen Knight; Thomas May (The University of Alabama, 2022)
We identify concerns pertinent to establishing trust necessary to support adoptees' confidence in and uptake of genetic testing that might allow them to benefit from early screening and medical intervention. Using principles of community-based participatory research, our study sought to build a foundation of trust to document such perspectives. Three focus groups were held with 12 adult adoptees. Transcripts were analyzed using thematic content analysis. Comments highlighted aspects related to genomics and health history in the context of adoption, specifically: (1) trust in the intention of the research study; (2) trust that the adoption community will benefit from the results of research; and (3) trust in the protection from misuse and abuse of genomic data. Results reinforce the call for proper security of data and oversight of the ways it is used and point to the value of including researchers who are a part of the community under study.